New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).